1999
DOI: 10.1523/jneurosci.19-20-j0005.1999
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Decomposition of Internal Models in Motor Learning under Altered Kinematic and Dynamic Environments

Abstract: The learning process of reaching movements was examined under novel environments whose kinematic and dynamic properties were altered. We used a kinematic transformation (visuomotor rotation), a dynamic transformation (viscous curl field), and a combination of these transformations. When the subjects learned the combined transformation, reaching errors were smaller if the subject first learned the separate kinematic and dynamic transformations. Reaching errors under the kinematic (but not the dynamic) transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(106 citation statements)
references
References 20 publications
10
95
1
Order By: Relevance
“…They showed that learning a visuomotor rotation is not affected by adaptation to an inertial load presented either simultaneously or 5 min later. Similarly, a recent study shows lack of anterograde interference between a visuomotor rotation and a viscous force field (Flanagan et al, 1999).In summary, these studies of motor interference have shown interference between two position-dependent visuomotor mappings and interference between two velocity-dependent force fields but no interference between a position-dependent visuomotor rotation and either an acceleration-dependent or velocitydependent force field. Based on these results, Krakauer et al (1999) concluded that internal models of kinematic and dynamic transformations are stored in distinct systems of working memory.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…They showed that learning a visuomotor rotation is not affected by adaptation to an inertial load presented either simultaneously or 5 min later. Similarly, a recent study shows lack of anterograde interference between a visuomotor rotation and a viscous force field (Flanagan et al, 1999).In summary, these studies of motor interference have shown interference between two position-dependent visuomotor mappings and interference between two velocity-dependent force fields but no interference between a position-dependent visuomotor rotation and either an acceleration-dependent or velocitydependent force field. Based on these results, Krakauer et al (1999) concluded that internal models of kinematic and dynamic transformations are stored in distinct systems of working memory.…”
mentioning
confidence: 51%
“…They showed that learning a visuomotor rotation is not affected by adaptation to an inertial load presented either simultaneously or 5 min later. Similarly, a recent study shows lack of anterograde interference between a visuomotor rotation and a viscous force field (Flanagan et al, 1999).…”
Section: Abstract: Motor Learning; Internal Models; Arm Movement; VImentioning
confidence: 69%
See 1 more Smart Citation
“…Finally, subjects have been studied performing reaching movements under novel environments while the kinematic and dynamic properties were altered [76,77]. The subjects were able to learn multiple internal kinematic and dynamic models that compensated for each transformation and, remarkably, were able to combine and decompose these models.…”
Section: Motor Learning and Adaptationmentioning
confidence: 99%
“…Neural mechanisms that mimic the input-output properties of objects support prediction and control; these are termed internal models (Kawato et al, 1987;Wolpert et al, 1995). Considerable evidence from behavioral, neurophysiological, and functional imaging studies indicates that the CNS maintains a number of internal models for different objects and environments in a modular manner (Ghahramani and Wolpert, 1997;Flanagan et al, 1999;Krakauer et al, 1999;Gribble and Scott, 2002;Imamizu et al, 2003;Yamamoto et al, 2007). Behavioral studies have shown that humans can switch internal models based on contextual information.…”
Section: Introductionmentioning
confidence: 99%